Transcriptome Analysis of Short-Day Photoperiod Inducement in Adzuki Bean (Vigna angularis L.) Based on RNA-Seq - Dong, Weixin; Li, Dongxiao; Zhang, Lei; Yin, Baozhong; Zhang, Yuechen (Frontiers in Plant Science, 2022)
The flowering characteristics of adzuki bean are influenced by several environmental factors. Light is an important ecological factor that induces flowering in adzuki bean, but to date, there have been few reports on the transcriptomic features of photoperiodic regulation of adzuki bean flowering. This study is based on RNA sequencing (RNA-seq) techniques to elucidate the expression of light-related regulatory genes under short-day photoperiod inducement of adzuki bean flowering, providing an important theoretical basis for its accelerated breeding. Short-day photoperiod inducement of 10 h was conducted for 5 d, 10 d, and 15 d periods on ‘Tang shan hong xiao dou’ varieties, which are more sensitive to short-day photoperiod conditions than the other varieties. Plants grown under natural light (14.5 h) for 5 d, 10 d, and 15 d were used as controls to compare the progress of flower bud differentiation and flowering characteristics. The topmost functional leaves that were unfolded were selected for transcriptome sequencing and bioinformatics analysis. The short-day photoperiod inducement promoted flower bud differentiation and advanced flowering time in adzuki bean. Transcriptomic analysis revealed 5608 differentially expressed genes (DEGs) for the combination of CK-5d VS SD-5d, CK-10d VS SD-10d, and CK-15d VS SD-15d. The three groups of the DEGs were analyzed using the Gene Ontology (GO) and Kyoto Encyclopedia of Genomes and Genomes (KEGG) databases; the DEGs were associated with flowering, photosystem, and the circadian rhythm and were mainly concentrated in the hormone signaling and metabolism, circadian rhythm, and antenna protein pathways. Thirteen light-related genes across the three pathways were screened for differential and expression characteristics, and these genes were found to be involved in the regulation of flowering time in adzuki bean through activating or repressing gene expression. Under short-day photoperiod inducement, the DEGs were mainly concentrated in the hormone signaling and metabolism, circadian rhythm, and antenna protein pathways and mainly regulated the flowering time of adzuki bean through upregulating the expression of genes. The findings provide a deep understanding of the molecular mechanisms of adzuki bean flowering in response to short-day photoperiod inducement, providing an important reference for molecular breeding of adzuki bean.